2021
DOI: 10.1111/bju.15383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enhanced optical techniques at time of transurethral resection of bladder tumour, with or without single immediate intravesical chemotherapy, on recurrence rate of non‐muscle‐invasive bladder cancer: a systematic review and network meta‐analysis of randomized trials

Abstract: To assess whether single immediate intravesical chemotherapy (SIIC) adds value to bladder tumour management in combination with novel optical techniques: enhanced transurethral resection of bladder tumour (TURBT). MethodsA systematic search was performed using the PubMed and Web of Science databases in September 2020 according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) extension statement for network metaanalyses. Studies that compared recurrence rates among intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…A recent systematic review and network meta‐analysis by Sari et al. sought to also assess whether a single intravesical chemotherapy installation added to the therapeutic effectiveness of BL and narrow‐band‐imaging‐assisted TURBT compared to WL [37]. The findings were consistent with ours in that BL TURBT outperformed WL, and the positive effect was accentuated by intravesical chemotherapy, as one might have expected.…”
Section: Discussionsupporting
confidence: 78%
“…A recent systematic review and network meta‐analysis by Sari et al. sought to also assess whether a single intravesical chemotherapy installation added to the therapeutic effectiveness of BL and narrow‐band‐imaging‐assisted TURBT compared to WL [37]. The findings were consistent with ours in that BL TURBT outperformed WL, and the positive effect was accentuated by intravesical chemotherapy, as one might have expected.…”
Section: Discussionsupporting
confidence: 78%
“…A recently published meta-analysis including 4,519 patients by Motlagh et al that focused on enhancement techniques during TURBT in NMIBC found that performing PDD during TURBT with concurrent single immediate intravesical chemotherapy (SIIC) resulted in superior recurrence outcomes. A significant reduction in 12- month recurrence rate performing PDD along with an increase in risk benefit by an additional 32% reduction in odds ratio was noticed when using concomitant SIIC ( 107 ).…”
Section: Resultsmentioning
confidence: 97%
“…Sari Motlagh et al [11 ▪▪ ] in recent systematic review and network meta-analysis included 22 studies with 4519 patients. The goal was to compare the recurrence rates of NMIBC depending on the type of tumour visualization during TURBT (WL vs. PDD vs. NBI) combined with single immediate intravesical chemotherapy (SIIC) administration (administered or not).…”
Section: Meta-analysesmentioning
confidence: 99%